PENGARUH BEBAN KERJA DAN INSENTIF TERHADAP KINERJA PEGAWAI DI UPTD PUSKESMAS NON RAWAT INAP AMBUKHA KECAMATAN LOLOFITU MOI KABUPATEN NIAS BARAT - Desna Wati Gulo (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study was to determine the effect of workload and incentives on employee performance at UPTD Ambukha Non-Inpatient Health Center, Lolofitu Moi District, West Nias Regency. The type of research used is quantitative research. The source of the data is from employees, with a population of 3 0 people and a sample of 30 people. The data collection technique is by distributing questionnaires to respondents, namely employees of UPTD Ambukha Non-Inpatient Health Center, Lolofitu Moi District, West Nias Regency. The data analysis method used is multiple linear regression analysis. The results of this study show that workload (X1) has a significant effect on employee performance (Y) where the workload variable (X1) obtained a calculated t-value (1, 2.878)>ttable(1.703) and a significance level of 0.000<0.05. Furthermore, the incentive variable (X2) has a significant effect on employee performance (Y) where the value of t iscalculated (13,006)>((1,703) and the ) significance level is ( 0.000<0.05 which means that partially the incentive variable (X2) has a significant effect on the employee performance variable (Y). The results of the simultaneous test (Test F), show that the value of F is calculated (245.321) > Ftable (3.35) and the ( level of significance is( 0.000<0.05, it can be stated that the variables workload (X1) and Incentive (X2) silmutant have a positive and significant effect on employee performance variables (Y). For the coefficient of determination (R 2) of 0.948, it can be interpreted that workload and incentives are only able to explain employee performance variables by 94.8% while the remaining 5,2% is explained by other variables not mentioned by the study.